CORPORATE GOVERNANCE: STATE OF THE ART - Darsono, Darsono (JURNAL BISNIS STRATEGI, 2001)
Since 1990s the good corporate governance (GCG) has becoming a part of critical issues, especially in the publicity held companies. In such condition, there is separation between principals and agent. The agent has opportunities to make decision that allow him to take advantages by principal's cost or agency cost. To minimize agency cost, principals build a control mechanism based on self-regulated and law. Corporate governance is mechanism to govern a company to fulfill shareholders interest. It consists of shareholder's role, board of commissioner's composition and role, board of director's composition and role, control mechanism, and reporting.